A block cipher based on genetic algorithm - Zakaria, Nur Hafiza (2016)
The development of block ciphers have resulted in a number of cryptographic algorithms such as, AES, ARIA, BLOWFISH256, DESL, 3D-AES and many more. In many algorithms which are based on the genetic algorithm approach, diffusion properties using crossover and mutation function are being generated to produce a secure data transmission. Permutation functions are components that are commonly used in block cipher to ensure that the ciphers are efficient. However, it would be more effective if we can use the optimum and suitable technique for crossover and mutation function. This research will concentrate on increasing the complexity and the efficiency of block cipher algorithm. This complexity can be done by designing an algorithm that consists of substitution function and permutation function which provides confusion and diffusion properties. Other than that, the evolvement of technology will also contribute towards the development of new block ciphers. To satisfy the information security requirements and to enhance the information security, we need secured communication and data which can be attained by encrypting the data. In this research, we proposed a new block cipher algorithm based on genetic algorithm approach which shall meet the security requirements. The study identifies the similarity elements and highlights the essential computation elements, namely crossover and mutation that generate idea to computational model. It can be applied in designing a new block cipher that fulfils Shanon’s confusion and diffusion properties. The structure of the components has a fixed block size which is 128 bits and a key size of 128 bits. There are three functions for each encryption process which are substitution function, crossover and mutation function and add round key function. In this research also, the algorithm has been tested with NIST Statistical Test suite to evaluate the randomness of the output. The avalanche effect or bit independence analysis has been carried out using correlation coefficient and key sensitivity in experiments and satisfies the confusion property in non-linearity transformation and sensitivity of the ciphertext generated in the block cipher. It also measures the diffusion property in cryptanalysis using branch number in estimating the possible success of differential and linear attacks. Based on the results, it is proven that the new proposed block cipher algorithm has successfully passed all the security requirements needed such as NIST Statistical Test, avalanche effect, cryptanalysis and efficiency to justify that it is a secure block cipher algorithm. Therefore, this new proposed block cipher can be used by countries, organizations, stakeholders or interested parties as one of the secure algorithm to increase the protection of the information and also will contribute as an alternative to other cryptographic algorithms in computer security research.